An approach to the sizing of electric motors devoted to aerospace propulsion systems. Issue 5 (26th August 2014) - Bouzidi, Ikhlas; Bianchi, Nicola; Masmoudi, Ahmed
Abstract : Purpose: – The purpose of this paper is to deal with the design and optimization of permanent magnet synchronous motors (PMSM) devoted to aeronautic applications. Design/methodology/approach: – A design approach as well as a performance investigation, based on two-dimensional finite element analysis of selected electromagnetic and thermal features, are applied to chosen PM synchronous machine topologies which differ by their number of phases. Findings: – It has been found that the initial set of geometrical parameters does not fulfill the torque/weight compromise required by a aeronautic applications since it leads to an average temperature rise higher than the authorized limit (class H: 155 K). Therefore, the sizing has been rethought in an attempt to meet the constraints of the considered application. Research limitations/implications: – Several continuations of the developed works shall be treated in the future, such as: (i) the prototyping of the designed machines, (ii) extending the optimization procedure to the whole drive including the motor and the associated static converter, and (iii) the synthesis and implementation of a dedicated control strategy with a suitable emulation of the load. Practical implications: – The studied machines could be integrated in aerospace propulsion systems. Originality/value: – The paper develops a design procedure of PMSM dedicated to aerospace applications where the compromise between torque/weight/temperature represents a crucial design challenge.